ANALISA PRODUKTIFITAS DAN LAJU DEKOMPOSISI SERASAH DAUN MANGROVE DI DESA BAHOI, KABUPATEN MINAHASA UTARA - Patty, Wehelmina (Sam Ratulangi University, 2010)
ABSTRACTPatty, W. 2010. Productivity Analysis and Litter Decomposition Rate Mangrove leaves in the Village Bahoi, North Minahasa Regency.Mangrove forest at Bahoi Village are still left under natural conditions, which are dominated by Sonneratia alba, Rhizophora apuculata and Bruguierra gymnorrhiza. The highest value of leaf decomposition rate found in R. apiculata (2 gr / week) and S. alba (1.75 gr / week). The leaves of S. alba species were decomposed most rapidly than R. apiculata. Analsysis productifity was based about 3 months data collections. Mean litter productivity is estimated Â± 2.55 gram/m2/ day. A large amount of organic materials from the mangrove can transfer into the sea by tides currents. Nutrients such as nitrate and phosphor are released to the water from mangrove sediments as result of deposit of organic matter.Keywords: productivity, mangrove, Minahasa Utara Regency